ANALYSIS OF GROWTH CENTER SYSTEM USING THE WEIGHT CENTRALITY INDEX METHOD (CASE STUDY OF KARAWANG DISTRICT) - Yuni Suryandari, Ratnawati; Rachmayarini, Ayu; Martina Kasikoen, Ken; Sofyandi, Herman (International Journal of Psychosocial Rehabilitation, 2020)
The development of Karawang Regency in general puts pressure on aspects of the environment, social life, economy and culture of the community, which originated from spatial locations that have a central and supporting role in it. This phenomenon is called spatial interaction which provides an overview of how to manage spaces based on their potential and problems and their relation to the surrounding space. This spatial interaction will form a certain hierarchical structure in an area based on indicators that describe the characteristics of each hierarchy. Karawang Regency consists of 309 villages spread across 31 subdistricts. The growth centers in Karawang regency basically will always be centered on locations with good public services. This will provide an attraction for the community in other locations which is one of the factors in the development of a location and has an influence on the location around it. In addition, the existence of transportation facilities in the form of toll roads and new railway lines makes it easier to access from and to Karawang Regency. Some of the problems in the Karawang regency have led to the growth of new centers. Based on these strategic issues, this study aims to determine the growth centers and their hierarchies in Karawang Regency by using an approach in the form of the Weighted Centrality Index method. And to find out how fast the development is happening in Karawang Regency, the data to be analyzed is the data in 2011 and 2014. In this study, the determination of the growth centers is at the smallest level of the village, while in the Karawang Regency Spatial Plan for the year period 2010-2030, determining growth centers based on urban centers at the sub-district level. Based on the results of the study, there is a difference between determining the hierarchy in this study with the urban spatial structure of Karawang Regency because this study uses the smallest area of the village, while the Regional Spatial Plan (RTRW) uses the smallest area of the district. Whereas in this study, the hierarchy of each village in one district varied.